Rational efficiency in agro-industrial process with cold chain: Thermodynamic and exergoeconomic measurement - Cely-Niño, Víctor Hugo; Cifuentes-Aya, Héctor; Torre-Marín, Gemma Cervantes (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The cold chain is the succession of links such as pre-cooling, refrigeration, freezing, and refrigerated transport. The physical variables of the heat transfer process are temperature control, relative humidity, dew point, and cooling surface. This paper aims at highlighting the use of thermodynamic tools such as exergy, anergy and entropy to measure rational efficiency in the different equipment and flows of a thermal process, through a transversal methodology that quantifies efficiencies in a relative, absolute, and comparative way. This study focused on the production structure of the agro-industrial cold chain by steam compression (refrigerant R404A), for the meat processing in channel, in the "Rastro Frigorífico Servicios Integrales del Bajío-TIF 333” in the city of Leon-Guanajuato, central region of Mexico. The results from the literature allowed to classify the critical points of greater exergy destruction, and the unproductive teams responsible for inefficiencies and residues production, which impact the hidden cost structure of the process, and affect negatively the process sustainability. This work integrates the thermoeconomic and productivity concepts that direct the nonlinear learning of thermodynamic science, relevant in the formation of an engineer.